2022
DOI: 10.3389/fcvm.2022.872833
|View full text |Cite
|
Sign up to set email alerts
|

Pregnant outcomes of critically ill pregnant patients with pulmonary hypertension: A multicenter retrospective study

Abstract: ObjectiveTo identify the pregnancy outcomes and risk factors of critically ill pulmonary hypertension (PH) patients with intensive care unit (ICU) admission.MethodsThe multicenter, retrospective cohort study was performed on 60,306 parturients from January 2013 to December 2018 in China. Diagnosis of PH was based on the estimation of systolic pulmonary arterial pressure (sPAP) via echocardiography. Patients were stratified by sPAP into three groups, mild (30–50 mmHg), moderate (51–70 mmHg), and severe (&gt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(7 citation statements)
references
References 26 publications
0
7
0
Order By: Relevance
“…In addition,7093 records were excluded for irrelevant articles (n = 3310),case series reports (n = 1201),conference articles(n = 1314) and other inappropriate article type(n = 1268) by looking at the title and summary. Of the remaining records, 98 records were deleted for various reasons, the original reports could not be retrieved(n = 12), inappropriate exposure (n = 25),inappropriate study design (n = 32) and inappropriate outcome indicators(n = 29).Finally,32 studies [ 9 40 ] with 2520 patients met the inclusion criteria (Fig. 1 ).…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…In addition,7093 records were excluded for irrelevant articles (n = 3310),case series reports (n = 1201),conference articles(n = 1314) and other inappropriate article type(n = 1268) by looking at the title and summary. Of the remaining records, 98 records were deleted for various reasons, the original reports could not be retrieved(n = 12), inappropriate exposure (n = 25),inappropriate study design (n = 32) and inappropriate outcome indicators(n = 29).Finally,32 studies [ 9 40 ] with 2520 patients met the inclusion criteria (Fig. 1 ).…”
Section: Resultsmentioning
confidence: 99%
“…Overall, 15 studies [ 11 – 22 , 38 40 ] were conducted, with 1,204 patients enrolled. Single-arm meta-analysis showed that the maternal mortality rates in the mild and moderate to severe groups were 0.15% (95%CI:0.00–0.93%) and 9% (95%CI:7–12%), respectively (Supplementary Fig.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations